Structure, properties, and in vitro behavior of heat-treated calcium sulfate scaffolds fabricated by 3D printing - Asadi-Eydivand, M.; Solati-Hashjin, M.; Shafiei, S.S.; Mohammadi, S.; Hafezi, M.; Abu Osman, Noor Azuan (Public Library of Science, 2016)
The ability of inkjet-based 3D printing (3DP) to fabricate biocompatible ceramics has made it one of the most favorable techniques to generate bone tissue engineering (BTE) scaffolds. Calcium sulfates exhibit various beneficial characteristics, and they can be used as a promising biomaterial in BTE. However, low mechanical performance caused by the brittle character of ceramic materials is themain weakness of 3DP calcium sulfate scaffolds. Moreover, the presence of certain organic matters in the starting powder and binder solution causes products to have high toxicity levels. A post-processing treatment is usually employed to improve the physical, chemical, and biological behaviors of the printed scaffolds. In this study, the effects of heat treatment on the structural, mechanical, and physical characteristics of 3DP calcium sulfate prototypes were investigated. Differentmicroscopy and spectroscopy methods were employed to characterize the printed prototypes. The in vitro cytotoxicity of the specimens was also evaluated before and after heat treatment. Results showed that the as-printed scaffolds and specimens heat treated at 300°C exhibited severe toxicity in vitro but had almost adequate strength. By contrast, the specimens heat treated in the 500°C-1000°C temperature range, although non-toxic, had insufficient mechanical strength, which was mainly attributed to the exit of the organic binder before 500°C and the absence of sufficient densification below 1000°C. The sintering process was accelerated at temperatures higher than 1000°C, resulting in higher compressive strength and less cytotoxicity. An anhydrous form of calcium sulfate was the only crystalline phase existing in the samples heated at 500°C-1150°C. The formation of calciumoxide caused by partial decomposition of calciumsulfate was observed in the specimens heat treated at temperatures higher than 1200°C. Although considerable improvements in cell viability of heat-treated scaffolds were observed in this study, the mechanical properties were not significantly improved, requiring further investigations. However, the findings of this study give a better insight into the complex nature of the problem in the fabrication of synthetic bone grafts and scaffolds via post-fabrication treatment of 3DP calciumsulfate prototypes.